Responses to organic pollutants in the tropical Pacific and subtropical Atlantic Oceans by pelagic marine bacteria - Vila-Costa, Maria; Lundin, Daniel; Fernández-Pinos, Maria-Carmen; Iriarte, Jon; Irigoien, Xavier; Piña, Benjamin; Dachs, Jordi (Frontiers in Environmental Science, 2023)
Background and chronic pollution by organic pollutants (OPs) is a widespread threat in the oceans with still uncharacterized effects on marine ecosystems and the modulation of major biogeochemical cycles. The ecological impact and toxicity of this anthropogenic dissolved organic carbon (ADOC) is not related to the presence of a single compound but to the co-occurrence of a myriad of synthetic chemicals with largely unknown effects on heterotrophic microbial communities. We have analyzed the metabolic capacity of metagenome-assembled genomes (MAGs) of natural oceanic communities from the north Pacific (Costa Rica dome) and Atlantic oceans challenged with environmentally relevant levels of ADOC. In the Atlantic, ADOC-exposed MAGs responded transcriptionally more strongly compared to controls than in the Pacific, possibly mirroring the higher relevance of ADOC compounds as carbon source in oligotrophic environments. The largest proportions of transcripts originated from MAGs belonging in the families Rhodobacteraceae and Flavobacteriaceae, known to play a role on consumption of several OPs. In the Atlantic, archaeal Poseidoniales showed the highest transcription levels after 2 hours of ADOC exposure, although no increase of relative abundances in the DNA pool was recorded after 24 hours, whereas Methylophaga showed the opposite pattern. Both taxa are suggested to be actively involved in the consumption of biogenic alkanes produced by cyanobacteria. We observed similar gene expression profiles of alkane degradation and methylotrophy signature genes. These findings, plus the chemical degradation of alkanes measured in the experiments, provides experimental evidence of the consumption of anthropogenic hydrocarbons and synthetic chemicals at the low concentrations found in the ocean, and modulation of microbiomes by ADOC.